2021
DOI: 10.21608/jpp.2021.205983
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Combining Ability and Type of Gene Action Using Half-Diallel Cross Among Seven S6 White Maize Inbred Lines

Abstract: Seven S6 white maize inbred lines were derived from selfing of S4 inbred lines of two populations; three way cross-324 and Giza-2 were used as parents of a 7 x 7 half-diallel cross and were obtained on 21 F1 crosses. These 7 S6 inbred lines and their 21 F1 crosses along with the 2 checks i.e., SC-128 and SC-129 were evaluated at Experimental Farm, Faculty of Agriculture, Al-Azhar University, Assiut Branch in 2021. Highly significant differences were detected among genotypes, parents, crosses, parents vs. cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Abd Results showed that variances of GCA and SCA were significant and highly significant for all studied traits except for SCA of EHT, indicating that additive and non-additive gene effects were important in the inheritance of most studied traits. Our results are relevant to those obtained by Bisen et al, (2020) and Abd EL-Zaher et al, (2021) for DTS and PHT, Onejeme et al, (2020) and Ramadan et al, (2022) for DTS, PHT and GY, Abd EL-Azeem et al, (2021) for DTS, PHT, Epos% and GY, Patil et al, (2021) for DTS and GY and Abdulla et al, (2022) for DTS and PHT. The ratio of GCA/SCA was more than unity for all studied traits except GY trait, indicating that the additive gene effects were more important and played major role in the inheritance of all studied traits except for GY trait.…”
Section: General (Gca) and Specific (Sca) Combining Ability Variancessupporting
confidence: 87%
“…Abd Results showed that variances of GCA and SCA were significant and highly significant for all studied traits except for SCA of EHT, indicating that additive and non-additive gene effects were important in the inheritance of most studied traits. Our results are relevant to those obtained by Bisen et al, (2020) and Abd EL-Zaher et al, (2021) for DTS and PHT, Onejeme et al, (2020) and Ramadan et al, (2022) for DTS, PHT and GY, Abd EL-Azeem et al, (2021) for DTS, PHT, Epos% and GY, Patil et al, (2021) for DTS and GY and Abdulla et al, (2022) for DTS and PHT. The ratio of GCA/SCA was more than unity for all studied traits except GY trait, indicating that the additive gene effects were more important and played major role in the inheritance of all studied traits except for GY trait.…”
Section: General (Gca) and Specific (Sca) Combining Ability Variancessupporting
confidence: 87%